Diseño de un sistema de gestión de calidad para la direción metropolitana administrativa del Municipio del Distrito Metropolitano de Quito - Legarda Sevilla, Mónica Alejandra (2012)
In this chapter one has been mentioned and determined all the theoretical part - conceptual, which is applied to the entire thesis document, which contains the same basic guidelines for the administration and management processes, from the application of their precursors as: Juran, Ishikawa, Crosby and Deming. Since they emit a general knowledge of what is meant the quality within the industries. In chapter two was performed, the diagnosis both external and internal administrative Metropolitan address, in which were used as strategic administrative tools are: the workshops of brainstorming within the DMA,the evaluation matrices of internal and external factors, which are the input of the SWOT matrix,